The android-based e-module development about dragonfly diversity around sri gethuk waterfall as biodiversity teaching material for Xth Grade of Senior High School - Puji Lestari Triatmanto; Triatmanto (Asian Journal Collaboration of Social Environmental and Education, 2023)
The aim of the study is to determine the feasibility of an android-based e-Module from dragonfly diversity data at Sri Gethuk Waterfall as biodiversity teaching material for Xth grade of Senior High School based on the results of expert assessment and readability test of biology teachers and students. This Research and Development (R&D) with the ADDIE model (Robert Maribe Branch, 2009) which is limited up to the ADD stage. The study subjects consisted of two material experts, three media experts, two high school biology teachers, and 25 Natural Science students of Xth grade. The object of the study was a prototype of android-based e-module about Dragonfly Diversity at Sri Gethuk Waterfall. The data collection assessment instruments for the material experts, the media experts, the biology teachers, and the students.The results show that some BSNP standard assessment criterias have not yet identified in the e-Module. The criterias that have not yet identified are then corrected according to expert advice and verified with credible academic sources, so that the criteria of e-module can be suitable with the standards. All of the criterias of e-Module that suitable with the standards are identified, so the e-Module can be used as teaching material in learning activities.